Uutta karjalan kielen tutkimusta - Lauttamus, Timo (Kotikielen Seura, 2001)
Kirja-arvioSarhimaa, Anneli: Syntactic transfer, contact-induced change, and the evaluation of bilingual mixed codes: Focus on Karelian-Russian language alternation